2022
DOI: 10.3390/ijerph191912123
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Use of Folic Acid Supplements during Pregnancy and Children’s Cognitive Function at 7–9 Years of Age in the INMA Cohort Study

Abstract: This study investigated the association between maternal low (<400 μg/day) or high (≥1000 μg/day) folic acid supplements (FAs) use during pregnancy and the attentional function and working memory in boys and girls at age 7–9. A longitudinal analysis based on 1609 mother–child pairs from the Spanish Infancia y Medio Ambiente Project was carried out. Multivariable regression analyses revealed that, compared to the recommended FAs use, a low FAs use during the second period of pregnancy was associated with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…There have been several studies investigating the sex-specific effects of prenatal folic acid supplement on offspring’s health outcomes. For example, a Spanish multicenter longitudinal study reported that low (<400 μg/day) folic acid supplements use during pregnancy was associated with poorer attentional function in girls and poorer working memory in boys, and high (≥1000 μg/day) folic acid supplement was associated with a better working memory only in girls [ 67 ]. Moreover, the effects of prenatal folic acid supplementation on body weight and insulin resistance were sex-dependent in a rat experiment, which showed that maternal folic acid supplementation could increase body weight and insulin sensitivity in male offspring, but decrease body weight and increase insulin sensitivity in female offspring [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies investigating the sex-specific effects of prenatal folic acid supplement on offspring’s health outcomes. For example, a Spanish multicenter longitudinal study reported that low (<400 μg/day) folic acid supplements use during pregnancy was associated with poorer attentional function in girls and poorer working memory in boys, and high (≥1000 μg/day) folic acid supplement was associated with a better working memory only in girls [ 67 ]. Moreover, the effects of prenatal folic acid supplementation on body weight and insulin resistance were sex-dependent in a rat experiment, which showed that maternal folic acid supplementation could increase body weight and insulin sensitivity in male offspring, but decrease body weight and increase insulin sensitivity in female offspring [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they also observed comparatively better cognitive and working memory among girls [61]. Another study conducted in Japan reports a higher cognitive, language, and social development quotient among 4-years-olds whose mothers began FA supplementation before week 12 of gestation [8].…”
Section: Early Childhood Cognitionmentioning
confidence: 91%
“…Moreover, periconceptional use of FA folic acid supplements < 0.4 mg/day or ≥ 1 mg/day has been shown to produce deficits in attentional function only in boys aged 4 -5 years [28]. Longterm follow-up (7 -9 years) of children born to mothers who used folic acid supplements beyond the periconceptional period identified deficits in attentional function different for boys and girls [29]. In contrast, the results of the 2006/2007 randomized controlled trial of 0.4 mg/day folic acid supplementation during the second and third trimesters (FASSTT) from the 14 th week of gestation to the end of pregnancy, showed at 7 years beneficial effects regarding children's cognitive performance [30].…”
Section: Drugs Administration In Pregnancy and Asd Riskmentioning
confidence: 99%